The Function of Baundi Tradition in Nagari Pandai Sikek, X Koto Sub-District, West Sumatra Province - khairunnisa, indah; Suharti; Mutia Kahanna (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Thesis entidled " Tradisi Baundi di Nagari Pandai Sikek Kecamatan X Koto Provinsi Sumatera Barat". Purpose this study is for describe the form of implementation baundi tradition and function from baundi Nagari Pandai Sikek Kecamatan X Koto Provinsi Sumatera Barat. The theory used in this thesis is Radcliffe Brown's structural functionalism. The method that the author uses is a qualitative method, with data collection techniques namely observation, interviews and documentation. Study result found that there are three stages in implementation baundi tradition is negotiating preparations (barundiang), said yes (mampaiyoan), and (mampamanggia). Implementation started from wich offering (pasambahan), baundi and last wich eating together. Next last stage also there are part function from implementation baundi tradition this is function from baundi this tradition is 1). kinship function, 2). family function, 3). education function, 4). cultural preservation function.